SENSE STRUCTURE OF MODAL UNITS “IMPROBABILE”, “CON OGNI PROBABILITÀ” (IN THE ITALIAN LANGUAGE) - Okhrimenko , Valeria (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article focuses on appropriateness’s of quantifying of information in microtext of functioning of modal units “improbabile” and “con ogni probabilità” in the Italian language. Modal units“improbabile” and “con ogni probabilità” determine quantifying of information in microtext being nucleus and forming modal structures together with joined components. The modal structure is formed by joined components in according to the regularity rules in the pre-nuclear zone (components combined with modal units “improbabile” and “con ogni probabilità”) and the near-peripheral zone (components used in the modal sentence with these modal units or in adjacent sentences). The modal meaning of epistemic probability is structured by the principle of graduation and implicates diverse degree to monocausality orientation. The factor of neutralization of opposition “imagination about reality vs correlation with reality” is epistemic state of subject of modal meaning. The linguistic means of expression of the modal meaning of epistemic probability are modal structures which contain quantors as reflection of measuring approach to reality. The prototype of modal meaning of epistemic probability is represented by modal units “probabilmente” (“probabile”, “probabilità”). The modal units “іmprobabile” and “con ogni probabilità” which sense structure is analyzed in this article present maximal deviation from prototype expressing, respectively, negation and affirmation of probability. The modal unit “improbabile” is a marker of maximal lowering of grade of probability of the modal evaluation by epistemic vector (complete contradiction between imagination about reality and a fragment of objective reality) and possesses its own specific sense structure. In the pre-nuclear zone of “improbabile” are used existential predicate “essere”, negative totality quantors “nessuno”, “mai”, adverbs meaning exceeding of quality measure (“estremamente”). In the near-periphery zone are used: mental predicate of point of view or mental predicate of knowledge in negative form (often preceded by approximator “quasi”), mental predicate of knowledge in impersonal form “non si sa mai”, lexical units meaning exclusivity of object evaluated as improbable, emotional reaction of extreme astonishment, attempts of verification. Epistemic vector of a microtext being verbalized contains contradiction between expectations of a subject of modal evaluation and reality. Emotive vector of a microtext being verbalized contains information about astonishment. Evaluative vector of microtext being verbalized contains information about exclusivity of a fragment of reality evaluated from the modal point of view. The modal unit “con ogni probabilità” is a marker of maximal increasing of grade of probability of the modal evaluation by epistemic vector (complete correlation between imagination about reality and a fragment of objective reality) and possesses its own specific sense structure. This fixed modal structure contains totality quantor in its structure that influences on verbalization of microtext vectors and their sense filling. In the near-periphery zone are used: existential predicate “essere”, verbs containing semes of exactitude and correlation (“corrispondere”), modal units of trustworthiness containing semes of exactitude and correlation (“proprio”, “esattamente”). Microtext usually verbalizes factual information so existential predicates are used more than mental ones. A principle of logical sequence that characterizes enunciations containing operation with facts influence type of cohesion of mictotext. Instead of causal connectors are used lexical units that significate local and time parameters of situation, a subject of modal evaluation and his probable actions that means removal of accents from gnoseology to ontology because the events are related from the point of view of neutral observer. Microtext can be divided in specification zone which contains operations with facts and generalization zone which contains an explicit deduction. __________ References: • Bondarko, A. V. «Temporal’nost’ [Temporality].» Teorija functsionalnoj grammatiki: Temporal’nost’. Modal’nost’ [Theory of functional grammar: Temporality. Modality] (Leningrag, Nauka, 1990), 263. • Bulygina,T. V., Shmelev, A. D. «“Pravda fakta” i “pravda bol’shih obobshhenij” [Truth of facts and truth of great generalizations].» Logicheskij analiz jazyka. Istina i istinnost’ v kul’ture i jazyke [Logical analyses of language. Trust and trustworthiness across languages and cultures] (Moskva: Nauka, 1995): 126-133 (In Russian). • Vendler, Z. «Facty v jazyke [Facts in languages].» Filosofija, logika, jazyk [Philosophy, logics, language] (Moscow, 1987): 293-317. • Kolesnikova, S. M. Funktsional’no-semanticheskaja kategorija gradual’nosti v sovremennom russkom jazyke [Functional-semantic category of graduality in contemporary Russian] (Moscow, 2010), 279. • Kustova, G. I. «Predicaty interpretatsiji: oshybka i narushenije [Predicates of interpretation: mistake and violation].» Logicheskij analiz jazyka. Jazyki etiki [Logical analyses of language. Ethics languages] (Moscow, 2000): 125-133. (In Russian). • Okhrimenko, V. I. Ontologija ta gnoseologija kategoriji modal’nosti v italijs’kij movi. Dokt, Diss [Ontology and gnoseology of the category of modality in Italian. Dokt, Diss] (Kyiv, 2012), • Il Dizionario della lingua italiana, 2-a ediz., Giacomo Devoto, Gian Carlo Oli (Firenze, Le Monnier, 2000-2001), • McGlone, S., Reed, A. B. «Anchoring in the interpretation of probability expressions.» Journal of Pragmatics 30 (Amsterdam, Elsevier, 1998): 723-733. • Vaidya, J., Wallner, M. «The epistemology of modality and the problem of modal friction.» New directions in the Epistemology of Modality (USA, 2018), https://link.springer.com/article/10.1007/s11229-018-1860-2#auth-Michael-Wallner (accessed 5.01.2021). • Schiavini, L. Senso unico: Tratto da: “Senso unico” di Laura Schiavini (Varese: ECO, 1997), http://www.lieberlieber.it/biblioteca/s/schiavini/senso_unico/pdf/senso_p.pdf • Chi: settimanale di politica, attualità e cultura 42, Silvana Giacobini (20.10.2004), 182. • Huffpost, Esteri, https://www.huffingtonpost.it/entry/covid-il-rapport-delloms-a-wuhan-esclude-la-fuga-del-virus-da-un-laboratorio_it_60616e13c5b67593e05a159a. • Oggi: settimanale di politica, attualità e cultura20, Paolo Occhipinti (18.05.2005), 162. • Vescovi Valtorta e Colombo: piano annuale per l’inclusività, https://www.valtortaecolombo.it/pai/ (accessed 20.03.2021).